HUBUNGAN PENGETAHUAN PUS TENTANG ALAT KONTRASEPSI MOW DENGAN MINAT PUS TERHADAP ALAT KONTRASEPSI MOW DI PRAKTEK BIDAN HJ. R. BATUBARA KOTA PADANGSIDIMPUAN TAHUN 2018 - MARYAM LATIFAH HARAHAP (JURNAL ILMIAH KOHESI, 2020)
Women's Surgical Medical Contraception (MOW) is a method of permanent contraception in women, performed with a smalloperation to tie / clamp / cut the fallopian tubes. The purpose of this study was to determine the relationship between thelevel of EFA knowledge about MOW with EFA interest in MOW contraceptives. This research uses descriptive analyticmethod with cross sectional research design. The sampling technique uses accidental sampling with a total sample of 46EFAs. Data were collected using a questionnaire. The analysis used is univariate analysis and bivariate analysis with chisquarestatistical test with confidence level (95% CI) and α = 0.05. The results of this study indicate a significant relationshipbetween EFA knowledge about MOW with EFA interest in contraception MOW (Pvalue = 0.007 <2 count = 9,807α = 0.05)and (> 2 table = 5.991). The conclusion is that there is a relationship between EFA knowledge about MOW with EFA interestin contraception MOW practice of midwife Hj. R. Coal of the city of Padangsidimpuan in 2018. Thus the authors propose anumber of suggestions, namely for respondents to be able to increase knowledge and add insight about MOW contraceptionby asking health workers, reading books, watching television and so on so that EFA know about MOW contraception.